English Development as a Second Language in Relation with TV Exposure - Widiastuti, Ni Made Ayu; Shanti Sari Dewi, Anak Agung Sagung; Isnu Maharani, Sang Ayu (Lingual Journal of Language and Culture, 2018)
The aims of this study are to know the role of young learner’s parents in choosing good and educating television program for their child, and to describe the effects of TV exposure in their child’s English language development. A five-year-old young learner who lives in Denpasar was observed in 2017. The data were collected by giving a questionnaire to the young learner’s parents in order to get the description of the effects of the television programs to her language development. As it is a following research of the previous research on English vocabulary acquisition, the results of the observation of the young learner and the interview with her parents that have already been done are used to support the analysis of this small research. The collected data were analysed descriptively based on approaches from Barr, et.al. (2010), Christakis (2009), and March (2004) about English language acquisition and language development of young children. The results show that the young learner’s parents have the important role in choosing good and educating television program for her. It can be seen from the choices of cartoon movies as one of the television programs that is educating as well as entertaining for a child in her age, the intensive accompaniment when she was watching the movies, the limitation of television watching time, and also the parents’ assistance in order to help her understand the stories and vocabulary meanings. It is true that good content, context, and the amount of daily TV viewing time as well as parental assistance will be beneficial for the young learner’s second language development in informal learning situation. The effectiveness of watching cartoon movies has led her to gain the positive second language development in her bilingual condition, although English code-switching in Indonesian sentences sometimes occur. Keywords: SLA, English, language development, TV exposure, cartoon movies